Chemistry of metalloproteins : problems and solutions in bioinorganic chemistry - Stephanos, Joseph J.; Addison, A. W. (Hoboken, New Jersey : Wiley, 2014)
"This question-and-answer guide on metalloproteins reflects the broad range of aspects within this branch of protein science. It is divided into seven parts, addressing: the cell, the alkali and alkaline earth cations, non-redox metalloenzymes, carboxypeptases, carbonic anhydrase, alcohol dehydrogenase, copper proteins, electronic and ESR spectra of copper ions, plastocyanin, stellacyanin, superoxide dismutase, electronic spectra of iron ions, Mossbauer spectroscopy of iron ions, ESR spectra of Iion (III), iron bioavailability, siderophores, non-heme iron proteins, ferritin, transferrin, dioxygenase-iron proteins, rubredoxin, 2Fe-2S Ferredoxins, 4FE-4S Ferredoxins and hiPIP, aconitase, hydroxylases, hydrogenases, nitrogenases, binuclear Fe proteins, hemerythrin, ribotide reductase, purple acid phosphate and methane mono-oxygenase, heme proteins, myoglobin and hemoglobin, electronic spectra of hemoproteins, cytochrome C, peroxidase, cytochrome P450, ESR spectra of hemoproteins, vitamin B12, and chlorophyll. Each section ends with suggestions for further reading"--Provided by publisher.
Electron Transfer in Porphyrins and MetalloporphyrinsCatalases; Peroxidases; Cytochrome P-450; Electronic Spectra of Hemoproteins; ESR Spectra of Hemoproteins; References; Chapter 6: Vitamin B12; References; Chapter 7: Chlorophyll; References; Index; End User License Agreement
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Metalloproteins -- chemistry -- Examination Questions; Metalloproteins -- Examinations, questions, etc; SCIENCE -- Life Sciences -- Biochemistry; Metalloproteins; Examination Questions; Electronic books; Examinations; Electronic books